2020
DOI: 10.1038/s41416-020-0954-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumour budding and its clinical implications in gastrointestinal cancers

Abstract: Tumour budding in colorectal cancer has become an important prognostic factor. Represented by single cells or small tumour cell clusters at the invasion front of the tumour mass, these tumour buds seem to reflect cells in a ‘hybrid’ state of epithelial–mesenchymal transition, and evidence indicates that the presence of these entities is associated with lymph node metastasis, local recurrence and distant metastatic disease. The International Tumour Budding Consensus Conference (ITBCC) has highlighted a scoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 103 publications
(119 reference statements)
1
52
0
1
Order By: Relevance
“…With regard to locally resected pT1 cancers, there was strong consensus that TB scoring should be routinely performed in practice, incorporated in national guidelines, and be factored into clinical decision-making. This is supported by strong evidence establishing intermediate and high TB (Bd2/Bd3) as independent predictors of LNM in pT1 CRC [28][29][30]. There was also consensus that locally resected pT1 cancers, in which intermediate or high TB was the only highrisk feature, should be discussed in a multidisciplinary meeting.…”
Section: Discussionmentioning
confidence: 88%
“…With regard to locally resected pT1 cancers, there was strong consensus that TB scoring should be routinely performed in practice, incorporated in national guidelines, and be factored into clinical decision-making. This is supported by strong evidence establishing intermediate and high TB (Bd2/Bd3) as independent predictors of LNM in pT1 CRC [28][29][30]. There was also consensus that locally resected pT1 cancers, in which intermediate or high TB was the only highrisk feature, should be discussed in a multidisciplinary meeting.…”
Section: Discussionmentioning
confidence: 88%
“…The relationship of high tumor budding score with aggressive tumor characteristics such as more advanced pT, pN and AJCC stages, lymphovascular and perineural invasions, distant metastasis and local tumor recurrence in colorectal cancer has been demonstrated in many studies of the literature. [8,9,[20][21][22][23][24] In the study of Kim et al conducted on 78 GBC patients; a higher TB score was found associated with a poorer histological differentiation, a higher pT stage, presence of LN metastasis as well as lymphatic, venous or perineural tumor invasion. [4] Similarly, Kai et al have also reported that presence of TB was significanly associated with advanced T stage, LN metastasis and venous invasion in GBC.…”
Section: Discussionmentioning
confidence: 96%
“…Recent evidence also suggested that these features are intertwined and could represent two sides of the same coin, ultimately leading to lymph node metastasis ( 21) since cells composing the tumor "buds" were found to be also responsible for the invasion of nearby stromal lymphovascular vessels. These cells exhibited epithelial and mesenchymal markers suggesting the activation of the epithelialmesenchymal transition process, an aggressive tumor phenotype associated with poor survival and resistance to therapy (37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%